Analysis of Customer Relationships on Consumer Satisfaction at Public Ports in Riau Archipelago Province - Wahyudi, Zulfikar; Yulfiswandi, Yulfiswandi; Donal Mon, Muhammad (Universitas Ibn Khladun Bogor, 2025)
This study aims to investigate the impact of trust, flexibility, communication, on on customer satisfaction with customer relationships as intervining variable in Kuala Raiu Port. The sample method employed is a non-probability sampling methodology. The study sample comprised 173 individuals who were employees of PT. Tuah Bainaura Perkasa and the Federation of Transport and Reform Workers Unions at the Kuala Riau Port. The employed research methodology is quantitative, Smart PLS is software used to analyze data using the Structural Equation Modeling Partial Least Squares technique. The findings indicate that the variables of trust, communication, and customer relationships exert a positive and significant influence on customer satisfaction, while the flexibility variable did not affect customer satisfaction, besides that trust, flexibility, communication had a positive and significant effect on customer relationships. While the results of the mediation analysis Customer relationships were able to act as a mediator between trust, and customer satisfaction. However, it has not been able to become a mediator for Flexibility and Communication on Consumer Satisfaction. This study highlights that enhancing trust, communication and customer relationship can enhance customer satisfaction, highlighting the important role of customer relationship as a mediating variable. The findings of this study provide practical implications for port management, highlighting the need to focus on these areas to enhance overall satisfaction by building strong relationships with customers and contributing to the literature by exploring the relationships among trust, flexibility, communication, customer relationship and satisfaction in the context of cargo port services.